Conceptualising impulse purchase elements for iTV advertising - Che Omar, Azizah; Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah (International Association of Computer Science and Information Technology Press (IACSIT), 2015)
This paper describes an ongoing study related to the conceptual design model of interactive television (iTV) advertising towards influencing impulse purchase tendency.It was found that most of the existing studies have proposed factors of impulse purchase in different advertising medium like website, mobile, traditional retail store and traditional television.However, none of the impulse purchase model is dedicated towards impulse purchase tendency for iTV advertising. Therefore, the objective of this study is to identify and eventually conceptualise impulse purchase elements that are suitable for iTV advertising. The method used for this study is content and comparative analysis from existing studies in order to get the impulse purchase elements.The findings show that the elements of impulse purchase are classified into nine categories; information, influence, emotion, attention, message, acceptance, still media, motion media and interactivity.The detail elaborations of the impulse purchase elements are discussed at the end of this paper.